A graphene titanium dioxide nanocomposite (GTNC): one pot green synthesis and its application in a solid rocket propellant1. Issue 78 (26th August 2015) - Dey, Abhijit; Nangare, Vinit; More, Priyesh V.; Shafeeuulla Khan, Md Abdul; Khanna, Pawan K.; Sikder, Arun Kanti; Chattopadhyay, Santanu
<x xml:space="preserve">Abstract</x> A green process was developed for a graphene–titanium dioxide nanocomposite (GTNC) synthesis by dispersing titanium dioxide (TiO2) nanoparticles and graphene nano-sheets (GNSs) in ethanol via ultrasonication followed by microwave irradiation.